ANTIOXIDANT AND HEPATOPROTECTIVE POTENTIALS OF BAUHINIA VARIEGATA SEEDS AGAINST FERRIC CHLORIDE-INDUCED LIPID PEROXIDATION IN CHICKEN LIVER HOMOGENATE - Tshidino, Shonisani Cathphonia; Montsho, Ntakadzeni (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Iron accumulation in the liver is customary in pathological conditions associated with oxidative stress. Iron is also an essential element for organisms at its physiological levels. This study was aimed at investigating the antioxidant and hepatoprotective potential of acetone and methanol defatted seed extracts of Bauhinia variegata Linn (Leguminosae) against ferric chloride (FeCl3)-induced lipid peroxidation in chicken liver in vitro.Materials and Methods: Antioxidant capacity and hepatoprotective potential of acetone and methanol defatted seed extracts of B. variegata were evaluated using the established in vitro models, FeCl3-induced lipid peroxidation in chicken liver homogenate and thin layer chromatography-2,2-diphenyl-1-picrylhydrazyl (TLC-DPPH). Ascorbic acid, and acetone and methanol seed extracts of milk thistle (Silybum marianum) were used as antioxidant and hepatoprotective controls. Results: An overall of 80% acetone and absolute methanol defatted seed extracts of B. variegata [B. variegata acetone extract (BVAc) and B. variegata methanol extract (BVMe)] revealed to possess antioxidant and free radical scavenging capacity, which can protect the liver from FeCl3-induced lipid peroxidation in a concentration-dependent manner when compared with controls, ascorbic acid and extracts of milk thistle. At concentrations of 250 µg/mL and 300 µg/mL, thiobarbituric acid reactive species (TBARS) inhibitions were 80.5% and 97.6% for BVAc; and 84% and 98.7% for milk thistle acetone extract (MSAc). At concentration of 300 µg/mL, BVMe and milk thistle methanol extract (MSMe) TBARS inhibitions were 89.0% and 93.8%, respectively. These findings may confirm the presence of antioxidant compounds with hepatoprotective potential in both defatted seed extracts of B. variegata. Conclusion: The findings of this study suggest acetone and methanol extracts of B. variegata defatted seeds may serve as good sources of natural antioxidant and hepatoprotective agents.